2018
DOI: 10.3389/fimmu.2018.02032
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Vagus Nerve Activation Modulates Immune Suppression in Sepsis Survivors

Abstract: Patients surviving a septic episode exhibit persistent immune impairment and increased mortality due to enhanced vulnerability to infections. In the present study, using the cecal ligation and puncture (CLP) model of polymicrobial sepsis, we addressed the hypothesis that altered vagus nerve activity contributes to immune impairment in sepsis survivors. CLP-surviving mice exhibited less TNFα in serum following administration of LPS, a surrogate for an infectious challenge, than control-operated (control) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…We therefore measured the expression of AID in NP-specific GC B cells. We have shown that CLP mice exhibit reduced serum TNF-α compared with sham mice when challenged with LPS (30). Previous studies suggest that AID expression is inducible and can be regulated by TNF-α in an NF-κB-dependent manner (31).…”
Section: Introductionmentioning
confidence: 72%
“…We therefore measured the expression of AID in NP-specific GC B cells. We have shown that CLP mice exhibit reduced serum TNF-α compared with sham mice when challenged with LPS (30). Previous studies suggest that AID expression is inducible and can be regulated by TNF-α in an NF-κB-dependent manner (31).…”
Section: Introductionmentioning
confidence: 72%
“…In addition, the CAP is recognized as a neuroprotective mechanism that is capable of reducing both systemic and cerebral inflammation, which further attenuates brain damage after activation [118,119]. Intriguingly, the vagus nerve is constitutively activated in septic survivors and appears to be associated with immune impairment and increased vulnerability to infections [120]. Therefore, the bidirectional changes in CAP activity deserve timely recognition and interference to eliminate potential hazards of the immune response.…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…The failure of efficient neuromodulation can lead to uncontrolled inflammation and irreversible damage to the central nervous system. Reconstruction of either HPA axis or CAP through administration of corticosteroids or stimulation of vagus efferent nerve, respectively, show great benefits for septic animals by ameliorating multiple organ damage and improving the survival [62,120]. In fact, deteriorative neuroinflammation is the center of the vicious cycle of SAE and immunosuppression because it arises from the aberrant response of immune system and acts as a key contributor to brain dysfunction.…”
Section: Sae Is a Vicious Cycle For Immunosuppression And A Future Pementioning
confidence: 99%
“…In a recent mouse study assessing the role of cholinergic innervation on inflammation, utilizing the cecal ligation puncture model, subdiaphragmatic vagotomy abolished immunosuppression noted in nonvagotomized mice. 27 The conclusion of the study was that cholinergic tone determines the immune balance, shifting between enhanced vagal nerve activation leading to an immunosuppressed phenotype and decreased vagal tone leading to inflammation. 27 Thus, the lack of innervation of nasal polyps, as noted in our study, may generate a pro‐inflammatory state by allowing for unchecked SCC expansion with a feed‐forward cycle of IL‐25 production.…”
Section: Discussionmentioning
confidence: 99%